Composición del Consejo Rector y género en las cooperativas turolenses - Gargallo Castel, Ana; Esteban Salvador, María Luisa; Pérez Sanz, Francisco Javier (REVESCO. Revista de Estudios Cooperativos, 2010)
In the last years, the number of works that analyse the situation of women on boars of directors in the profit and not for profit organizations has increased. Although the literature is scary and more extended out of Spain the number of studies in our country is increasing. According to some authors in the called democratic participation companies the direct implication of women in management is bigger than in others organizations. A bigger number of women on boards of cooperatives can help to improve the employ conditions and to get an economic, social and cultural balance in this type of organizations. In this paper we analyze the presence of women on the boards of these entities and we compare with the types of cooperatives managed by women with the aim of check if there are associations among them. At the same time, we connect the time of starting the cooperative with the female participation to seek the evolution of the responsibility of women in different interval.